POTENSI PRIVATE LABEL DALAM MENARIK MINAT KONSUMEN PADA BISNIS RETAIL - UNTUNG, DIANNA SARI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Intense competition between retailer coupled with a dynamic marketing environment requires the retailer to set the right marketing strategies evaluated. One of these strategies is private label products. Private label products can be attraction for consumers and drive buying decisions on high hanging low attractiveness for private label consumer products. Private label products that have a number of advantages compared to other products, especially on product attributes and price. This product attributes and product quality concerns regarding the price also competitive prices. Quality products that compete with lower prices possible to drive the consumer purchase decision. Various forms of superiority of private label products will be able to provide traction for consumer purchase. Consumer purchase decisions through a number of evaluations until the product range with an attractive attribute in particular price and quality will be able to encourage consumer purchase decisions. Nonetheless, private label products also need to have standardized quality to be accepted by consumers. in making a purchase of a product, then the post-purchase evaluation will determine consumer buying behavior further. When the post-purchase evaluation creates satisfaction, then repeat purchases will be created for private label products.